Innovative Strategies to Decompose Pollutants - Fabrizio Olivito; Pravin Jagdale (Toxics)
In an era marked by growing environmental awareness and a global commitment to achieving carbon neutrality, many human activities continue to contribute significantly to the pollution of water, soil, and air through the release of both organic and inorganic contaminants [...]